2018
DOI: 10.11604/pamj.2018.31.194.14425
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of serum trace element levels in women with invasive cervical cancer in Lagos, Nigeria

Abstract: Introduction Trace elements although present in minute quantities in human blood, they play a vital role in many biochemical enzymatic reactions and have been examined critically as a potential key factor in various human diseases including cancers. This study was aimed to determine the association between serum levels of trace elements and invasive cancer of the cervix. Methods This was an analytical cross-sectional study carried out among women seen at the Lagos Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…In more than 10% of the population, intake of zinc with meals is less than half the recommended dose, and chronic zinc deficiencies significantly increase the risk of cancer [10,12,13]. Many patients with cancer, especially of the lungs, breast, head, and neck, have a decreased level of zinc in the blood [14,15,16,17,18,19,20,21,22]. Due to the multitude of functions performed by this element, it can be assumed to play a leading role in defending against the initiation and promotion of tumors, although the mechanism of this role is not fully known [23].…”
Section: Introductionmentioning
confidence: 99%
“…In more than 10% of the population, intake of zinc with meals is less than half the recommended dose, and chronic zinc deficiencies significantly increase the risk of cancer [10,12,13]. Many patients with cancer, especially of the lungs, breast, head, and neck, have a decreased level of zinc in the blood [14,15,16,17,18,19,20,21,22]. Due to the multitude of functions performed by this element, it can be assumed to play a leading role in defending against the initiation and promotion of tumors, although the mechanism of this role is not fully known [23].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, increased concentration of copper is associated with various cancers, the present study data supports this as increased concentration of serum copper was found in the cancer patients. 7 Interestingly, the outcome of trace elements analysis showed that supplementation of AMM to cancer patients increased the concentration of selenium and zinc by 27-30% and 7-13%, respectively. On the other hand supplementation of AMM to cancer patients decreased the elevated copper concentration by 5-8%.…”
Section: Figure 4: Effect Of Amm and Methotrexate On In Vitro Prolifementioning
confidence: 99%
“…So a concern has logically developed as to whether exogenous antioxidant compounds taken concurrently during chemotherapy could reduce the beneficial effect of chemotherapy on malignant cells. [4][5][6][7] Several clinical trials have produced conflicting results regarding the benefit of antioxidants in cancer therapy thus questioning the incorporation of these substances in standard treatment regimens. 4,5 On the contrary literature survey of recent review articles for exploring the armoury of obscurity on concurrent use of antioxidant during chemotherapy revelled that antioxidant does not interfere with chemotherapy, they enhance the cytotoxic effect of chemotherapy, they protect normal tissue and increases patient survival and therapeutic response.…”
Section: Figure 4: Effect Of Amm and Methotrexate On In Vitro Prolifementioning
confidence: 99%
See 1 more Smart Citation
“…A large number of epidemiologic studies have been made to identify the risk factors for cancer. Among these, an association with trace elements has received considerable attention 28 . Elements like selenium, zinc, arsenic, cadmium, and nickel, are found naturally in the environment, and human exposure derives from a variety of sources, including air, drinking water, and food.…”
Section: Introductionmentioning
confidence: 99%